2004
DOI: 10.1186/1471-2334-4-35
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial outbreak of neonatal Salmonella enterica serotype Enteritidis meningitis in a rural hospital in northern Tanzania

Abstract: Background: Clinicians at Haydom Lutheran Hospital, a rural hospital in northern Tanzania noted an unusually high case-fatality rate of pediatric meningitis and suspected an outbreak of an unknown agent or an organism resistant to the empirical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 11 publications
1
26
1
1
Order By: Relevance
“…20 Salmonella Enteritidis PFGE has been used in epidemiological studies of sporadic, large salmonellosis and nosocomial outbreaks caused by this serotype, and it had revealed the same pattern regarding the isolates involved and confirmed the vehicle of infection. 1,2,9,24 Even though it has been suggested that PFGE has a limited value in epidemiological analysis due to the fact of the high genetic homogeneity among strains of this serotype, 23 our study found a considerable DNA level homogeneity among S. enterica serovar Enteritidis isolates. We obtained 17 patterns, S. En0001 being the predominant one with permanent circulation in the city and in all institutions that submitted isolates.…”
Section: Discussioncontrasting
confidence: 59%
“…20 Salmonella Enteritidis PFGE has been used in epidemiological studies of sporadic, large salmonellosis and nosocomial outbreaks caused by this serotype, and it had revealed the same pattern regarding the isolates involved and confirmed the vehicle of infection. 1,2,9,24 Even though it has been suggested that PFGE has a limited value in epidemiological analysis due to the fact of the high genetic homogeneity among strains of this serotype, 23 our study found a considerable DNA level homogeneity among S. enterica serovar Enteritidis isolates. We obtained 17 patterns, S. En0001 being the predominant one with permanent circulation in the city and in all institutions that submitted isolates.…”
Section: Discussioncontrasting
confidence: 59%
“…These observations could be part of the explanation for the high rates of nosocomial infections, where antibiotics are abundantly used. In fact, nosocomial Salmonella enterica infections, particularly with multidrug-resistant strains, are a concern in developing countries (22,42) and occasionally even happen in developed countries (18,33). Although our findings cannot be indiscriminately extrapolated to all diseases where microbiota imbalance has been implicated in the etiology, they show that, at least in infectious colitis, microbial imbalance precedes the onset of pathology rather than being the result of it.…”
Section: Discussionmentioning
confidence: 43%
“…[4][5][6] Despite the importance of HAI, there is no clear indication of the magnitude of the problem in most African countries-south of the Sahara. Published data on HAI from Sub-Saharan Africa are mainly on outbreaks of nosocomial infection [7][8][9][10][11][12] or are related to problems with various procedures. [13][14] The British national survey protocol 15 have been used in several British hospitals and detailed methodology is available therefore it was selected for this survey.…”
Section: Introductionmentioning
confidence: 99%